Analysis of Financial Problems of Wind Farms in Poland - Joanna Wyrobek; Łukasz Popławski; Maria Dzikuć (Energies, 2021)
Wind energy has been operating in Poland for over 20 years, but many opinions on its profitability are based on publications from other countries and simulations prepared by manufacturers. However, the truth is that the climatic specificity of various countries and price relationships, especially energy prices and subsidies, significantly differentiate this profitability depending on the country. The publication aimed to look at the profitability of wind farms in Poland from three perspectives: financial analysis, NPV (Net Present Value) calculation for older wind farms (2006–2014), and break-even price of energy for these farms (for a non-negative NPV). The research hypothesis set out in the publication stated that wind farms from this period require higher energy prices than current market prices in Poland to achieve a return on invested capital. An element of novelty was calculating the energy price range that would provide an opportunity for at least some of the older farms operating in the green certificates scheme to achieve a positive NPV. We also attempted to demonstrate that the loss of control over the prices of green certificates, which took place in 2014–2017, led to such a decrease in energy prices that the 2006–2014 wind farms suffered a net loss.